Synthesis and characterization of silica ceramic membranes via sol-dip coating - Kahlib, Nor Amyra Zulianey; Mohd Daud, Farah Diana; Mel, Maizirwan; Ahmad Azhar, Ahmad Zahirani; Hassan, Noor Azlina (Penerbit Akademia Baru, 2017)
The application of inorganic membrane as one of the methods for gas separation process has proven to show the greatest potential when compared to other methods. Ceramic membranes are considered as one of the many high potential inorganic membranes for this purpose. Current development of ceramic membrane focuses on the reduction of pore size for ceramic membrane up to nanometer scale without pinholes or cracking. Thus, in recent work, the silica ceramic membranes via sol dip-coating have been synthesized by using tetraethylorthosilicate (TEOS), distilled water and ethyl alcohol as sol. The influences of number of dipping have been examined. X-ray diffraction (XRD) results of the fabricated silica membrane show the presence of silica element and that each membrane possesses a periodic structure with each number of dipping. The IR adsorption from Fourier transform infrared spectrometry (FTIR) indicates the presence of functional group O-Si-O and Si-CH3. The intensity of these functional groups increases as the dipping time increase. Field Emission Scanning Electron Microscope (FESEM) results show that the number of visible pores on the surface of the ceramic support diminished after modification of ceramic membrane, with the number of silica particles increasing linearly with number of dipping. Thus, the synthesized silica ceramic membrane with good structure and chemical properties has shown great potential for biogas separation application.